Kajian Pemanfaatan Limbah Sabut Kelapa Menjadi Larutan Mikroorganisme Lokal - DHARMA, PUTU ANANTA WIDHIA; SUWASTIKA, ANAK AGUNG NGURAH GEDE; SUTARI, NI WAYAN SRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.2, April 2018, 2018)
Study of Coconut Husk Waste Utilization Become Local Microorganism Fermented Solution The coconut husk has the most component in the coconut fruit, it cover 35 % of their composition. The research aim to understand the impact of the substrate dose, fermentation period and interaction between factors in quality measurement of local microorganism solution. This research use randomized block design and factorial treatment arrangement. Parameter measurement in research were C organic, total N, C/N ratio, available P and K, C/P ratio, pH, salinity, total bacterial population and total fungi population. The result of the research show that significant interaction between factor with exception on total N. Overall dose of substrate show that the 300 grams and three weeks fermentation has the best result.